Zeolite membrane composite, method for producing the same, and method for producing methanol using the same

JP2026168973APending Publication Date: 2026-10-16MITSUBISHI CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025062565
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-04
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、メタノールガス/水素ガスのパーミエンス比の高いゼオライト膜複合体、該ゼオライト膜複合体の製造方法、該ゼオライト膜複合体を用いたメタノールの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026168973000003
    Figure 2026168973000003
  • Figure 2026168973000004
    Figure 2026168973000004
  • Figure 2026168973000005
    Figure 2026168973000005
Patent Text Reader

Abstract

To provide a zeolite membrane composite with a high methanol gas / hydrogen gas permeance ratio, a method for producing the zeolite membrane composite, and a method for producing methanol using the zeolite membrane composite. [Solution] A zeolite film composite having a zeolite film on a porous support, wherein the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° in an asymmetric reflection measurement with a fixed incident angle θ1 is 1 or more than the peak intensity around 2θ = 23.1°.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a zeolite membrane composite and a method for producing methanol using the same for methanol separation.

Background Art

[0002] Methods for producing methanol from a gas containing hydrogen and carbon monoxide (hereinafter sometimes referred to as "syngas") have been known for a long time, and examples thereof include methods using copper-based catalysts (copper-zinc based catalysts, copper-chromium based catalysts). The reaction for producing methanol from syngas is an equilibrium reaction, and is more advantageous at lower temperatures and higher pressures. However, since the reaction rate decreases at lower temperatures, general methanol production processes are carried out under harsh conditions of 200 to 300°C and 5 to 10 MPaG (or higher pressures), which not only consumes a large amount of energy during methanol production but also has many facility-related restrictions.

[0003] As a method for efficiently producing methanol, a plurality of methods have been proposed in which methanol is removed from the reaction system to shift the gas composition in the reactor away from the equilibrium composition, and the reaction is carried out at a conversion rate exceeding the equilibrium conversion rate.

[0004] Further, Patent Documents 1 to 4 propose methods in which a separation membrane is installed in a methanol synthesis reactor, and methanol and water are removed from the reaction system using the separation membrane, so as to increase the conversion rate beyond the equilibrium conversion rate.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

[0006] Patent Document 1 describes a lithium-ion-doped perfluorinated polysulfonic acid membrane as a methanol separation membrane. Patent Document 2 describes a porous graphite membrane, and Patent Document 3 describes a zeolite separation membrane of MFI type zeolite with a Si / Al ratio of 50 or more. Patent Document 4 describes preventing catalyst degradation by selectively removing water. However, while these methods were sufficient for separating carbon dioxide and methanol, separating hydrogen and methanol proved difficult, resulting in a low methanol / hydrogen gas permeance ratio, posing a challenge for further improvement. The inventors of the present invention investigated how to solve this problem by forming a dense, gapless film, but found that even when a sufficiently dense film was created, the permeance ratio was insufficient. Therefore, the object of the present invention is to provide a zeolite membrane composite with a high methanol gas / hydrogen gas permeance ratio, a method for producing the zeolite membrane composite, and a method for producing methanol using the zeolite membrane composite. [Means for solving the problem]

[0007] Blocking at the zeolite film surface is effective in inhibiting the permeation of hydrogen gas, which has a small molecular diameter. It is widely known that forming a film oriented towards the crystal plane facing the 10-membered ring pore, such as the (010) plane of MFI-type zeolite, increases the permeation rate of gases and liquids. The inventors focused on the orientation of the crystal plane and found that by weakening the orientation to a specific crystal plane on the zeolite film surface, they could suppress the permeation of hydrogen gas and enable the selective permeation of methanol gas. Furthermore, by creating a two-layer structure in which the crystal plane orientation differs between the zeolite film surface and the interior, they improved the diffusibility of methanol gas and achieved a result that does not inhibit permeation.

[0008] The formation of a two-layer zeolite film requires control of the boundary between the layers. The inventors attempted to set the surface of a porous support that supports the zeolite film as the boundary and grow crystal planes with different orientations on and inside the porous support. After diligent research, they found that a two-layer zeolite film can be formed by supporting seed crystals smaller than the pore diameter of the porous support inside the pores of the porous support.

[0009] The present invention is as follows: [1] A zeolite membrane composite having a zeolite membrane on a porous support, wherein the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° in an asymmetric reflection measurement with a fixed incident angle θ1 is 1 or more than the peak intensity around 2θ = 23.1°. [2] The zeolite membrane composite described in [1] above, wherein the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° in a symmetric reflection measurement without fixing the incident angle θ2 is 0.65 times or more and less than 1.00 times the peak intensity around 2θ = 23.1°. [3] The zeolite membrane composite according to [1] or [2] above, characterized in that the zeolite is of the MFI type. [4] A method for producing a zeolite membrane composite in which a zeolite membrane is formed on a porous support, wherein the D50 in the particle size distribution of the seed crystal is 90% or less of the central pore diameter of the porous support. [5] A method for producing a zeolite membrane composite according to [4] above, using a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw material, alkali metal atom raw material and water; a second step of mixing silicon atom raw material; a third step of heating the mixture after the second step at 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step. [6] A method for producing methanol, wherein a raw material gas containing at least hydrogen, and carbon monoxide and / or carbon dioxide is reacted in a reactor in the presence of a catalyst to obtain methanol, wherein the methanol generated by the reaction is permeated through and taken out from the zeolite membrane composite according to any one of the above [1] to [3].

Effects of the Invention

[0010] According to the present invention, it is possible to provide a zeolite membrane composite having a high methanol gas / hydrogen gas permeance ratio, a method for producing the zeolite membrane composite, and a method for producing methanol using the zeolite membrane composite.

Brief Description of the Drawings

[0011] [Figure 1] Figure 1 is an explanatory diagram showing an example of the method for producing methanol using the zeolite membrane composite of the present invention. [Figure 2] Figure 2 is the asymmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 1 of Example 1 of the present invention. [Figure 3] Figure 3 is the symmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 1 of Example 1 of the present invention. [Figure 4] Figure 4 is the asymmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 2 of Example 2 of the present invention. [Figure 5] Figure 5 is the symmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 2 of Example 2 of the present invention. [Figure 6] Figure 6 is the asymmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 3 of Comparative Example 1 of the present invention. [Figure 7] Figure 7 is the symmetric reflection measurement result of the X-ray structural diffraction pattern for the zeolite membrane composite 3 of Comparative Example 1 of the present invention.

Modes for Carrying Out the Invention

[0012] Hereinafter, typical embodiments for carrying out the present invention will be specifically described, but the present invention is not limited to the following embodiments as long as it does not exceed the gist thereof, and can be implemented with various modifications.

[0013] The zeolite membrane composite according to the embodiment of the present invention is a zeolite membrane composite having a zeolite membrane on a porous support, wherein the peak intensity near 2θ=23.7° in the X-ray diffraction pattern in asymmetric reflection measurement with a fixed incident angle θ1 is 1 time or more the peak intensity near 2θ=23.1°.

[0014] In X-ray structure diffraction analysis in asymmetric reflection measurement, the X-ray incident angle is fixed during a single measurement, and the incident angle is changed for each measurement to perform multiple measurements, thereby controlling the X-ray incident angle. The X-ray incident angle θ1 when the incident angle is gradually reduced until no peaks derived from the zeolite membrane are detected is defined as 0°, the incident angle is gradually increased from 0°, and the X-ray incident angle at which the peak of the porous support starts to be detected is defined as the maximum incident angle transmitting through the zeolite membrane, which is taken as the angle for measurement of the zeolite membrane.

[0015] The obtained X-ray diffraction pattern is smoothed using analysis software, Kα2 rays are removed, and peak detection is performed using the second derivative method. The obtained peaks are visually confirmed to ensure accurate detection, so that the error in the integrated intensity between the actual peak and the detection peak is within 5%. When changing the incident angle, the height of the membrane surface is fixed so that the same position of the membrane is irradiated with X-rays. For the value of integrated intensity, the value calculated by the software for the detection peak is adopted, and for the value of peak intensity, the value calculated by the software for the detection peak is adopted.

[0016] According to "COLLECTION OF SIMULATED XRD POWDER PATTERNS FOR ZEOLITE Fourth Revised Edition 2001 ELSEVIER," the peak around 2θ = 23.7° in the X-ray diffraction pattern originates from the plane with index (151) in the MFI structure, when the space group is Pnma (No. 62). In this specification, "peak around 2θ = 23.7°" refers to the largest peak among the peaks that do not originate from the support material and are located in the range of 23.7° ± 0.2°.

[0017] According to "COLLECTION OF SIMULATED XRD POWDER PATTERNS FOR ZEOLITE Fourth Revised Edition 2001 ELSEVIER," the peak around 2θ = 23.1° in the X-ray diffraction pattern originates from the plane with an index of (501) in the MFI structure, when the space group is Pnma (No. 62). In this specification, "peak around 2θ = 23.1°" refers to the largest peak among the peaks that do not originate from the porous support and are located in the range of 23.1° ± 0.2°.

[0018] In other words, the fact that the ratio of the peak intensity around 2θ=23.7° to the peak intensity around 2θ=23.1° in the X-ray diffraction pattern in asymmetric reflection measurements falls within the above range indicates that the orientation of the (501) plane is equal to or weaker than that of the (151) plane near the surface of the zeolite film. Due to this orientation of the crystal planes near the surface of the zeolite film, the zeolite film composite suppresses the permeation of hydrogen gas and selectively permeates methanol gas, i.e., it has a high methanol gas / hydrogen gas permeation ratio.

[0019] In the above asymmetric reflection measurement, the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° is preferably at least 1 times the peak intensity around 2θ = 23.1°, more preferably 1.1 times or more, more preferably 1.2 times or more, and even more preferably 1.3 times or more, from the viewpoint of increasing the methanol gas / hydrogen gas permeance ratio. Furthermore, from the viewpoint of improving the permeability of methanol gas, it is preferably 3.0 times or less the peak intensity around θ = 23.1°, more preferably 2.5 times or less, and even more preferably 2.0 times or less. The zeolite film composite of the present invention can be adjusted to a desired range by using the manufacturing method described later, by adjusting the peak intensities of the X-ray diffraction pattern around 2θ = 23.7° and around 2θ = 23.1° in the asymmetric reflection measurement.

[0020] In the embodiment of the present invention, it is preferable that the zeolite film composite in the X-ray diffraction pattern in a symmetric reflection measurement without fixing the incident angle θ2 has a peak intensity around 2θ = 23.7° that is 0.65 times or more and less than 1.00 times that of the peak intensity around 2θ = 23.1°.

[0021] X-ray structural diffraction analysis in symmetric reflection measurements can be performed using the same methods, apparatus, and conditions as the X-ray structural diffraction analysis in asymmetric reflection measurements described above, except that the angle of incidence of the X-rays is not fixed.

[0022] The fact that the ratio of the peak intensity around 2θ=23.7° to the peak intensity around 2θ=23.1° in the X-ray diffraction pattern in symmetric reflection measurements falls within the above range indicates that in the zeolite film composite, the orientation of the crystal planes differs between the area near the zeolite film surface obtained from asymmetric reflection measurements and the interior of the film obtained from symmetric reflection measurements. The interior of the film has a higher orientation towards the (501) plane, which favors diffusion and allows methanol gas to permeate easily.

[0023] In the above symmetric reflection measurement, the peak intensity of the X-ray diffraction pattern around 2θ=23.7° is preferably 0.65 times or more, more preferably 0.70 times or more, and even more preferably 0.75 times or more, of the peak intensity around 2θ=23.1°, from the viewpoint of increasing the methanol gas / hydrogen gas permeance ratio. Furthermore, since the high orientation to the (501) plane is advantageous for methanol gas permeation, it is preferably less than 1.00 times, more preferably 0.95 times or less, and even more preferably 0.90 times or less. The zeolite membrane composite of the present invention can be adjusted to a desired range by using the manufacturing method described later, thereby adjusting the peak intensities around 2θ=23.7° and 2θ=23.1° of the X-ray diffraction pattern in the above symmetric reflection measurement.

[0024] The standard measurement method for X-ray structural diffraction analysis used in the examples is shown below.

[0025] (Device) Device name: RINT-UltimaIII manufactured by Rigaku Corporation Optical System Specifications: Parallel Beam Optical System Vertical Goniometer D990825A03 Incident side: Sealed X-ray tube (CuKα) Soller Slit (Flexible Optics, 5°) Divergence Slit (Variable Slit) Light receiving side: Monochromator Long slits Ni-Slit

[0026] (Measurement conditions) X-ray output (CuKα): 40kV, 30mA Scan axis: θ / 2θ Scanning range (2θ): 22.0~26.0° Measurement mode: Continuous Reading width: 0.01° Scan speed: 1° / min Divergence slit: 1.0 mm Divergence vertical limiting slit: 5mm Scattering slit: Release Light-receiving slit: Open Offset angle: 0° h:0 k:0 l:0

[0027] (Analysis conditions) Software name: PDXL 2 version 2.4.2.0, manufactured by Rigaku Corporation. Baseline setting method: Sonneveld-visser method Nodes are set so that the distance between nodes is between 2 and 6 degrees, and there are no peaks. Each peak is detected using PDXL2. The detected peaks were visually confirmed, and the detection reference point was adjusted to match the measured peak. The integrated intensity value and the peak intensity value were both calculated using software. When performing the measurement, the sample should be set up so that X-rays are irradiated in a direction parallel to the axial direction of the cylindrical membrane composite, and the upper end of the sample should be set up to be at the same height as the measurement surface of the device.

[0028] [Zeolite membrane complex] The zeolite membrane composite of the present invention has a zeolite membrane on a porous support.

[0029] <Porous support> The porous support used in the present invention can be made of various materials, but is preferably an inorganic porous material. Specific materials that can be used include alumina, titania, zirconia, and silica, but is preferably alumina. Regarding the pores of the porous support, there are no particular limitations as long as macropores are present and do not prevent the zeolite membrane from forming properly; commonly used materials can be used.

[0030] <Zeolite membrane> The zeolite used to constitute the zeolite film in the present invention is not particularly limited as long as it contains aluminum, but the main zeolite constituting the zeolite film is preferably one that contains a zeolite having a pore structure with 12 or fewer oxygen rings and 6 or more oxygen rings. In this context, the value of n in zeolites having an n-membered oxygen ring indicates the largest number of oxygen atoms in the pores composed of oxygen and T elements (elements other than oxygen that make up the zeolite framework). For example, if pores with both 12-membered and 8-membered oxygen rings exist, as in MOR-type zeolites, it is considered a zeolite with a 12-membered oxygen ring.

[0031] Zeolites having a pore structure with 12 or fewer oxygen rings and 6 or more oxygen rings are defined by the International Zeolite Association (IZA) as follows, for example, AEI, AEL, AFI, AFG, ANA, ATO, BEA, BRE, CAS, CDO, CHA, CON, DDR, DOH, EAB, EPI, ERI, ESV, EUO, FAR, FAU, FER, FRA, HEU, GIS, GIU, GME, GOO, ITE, KFI, LEV, LIO, LOS, LTA, LTL, LTN, MAR, MEP, MER, MEL, MFI, MON, MOR, MSO, MTF, MTN, MTW, MWW, NON, NES, OFF, PAU, PHI, RHO, RTE, RTH, RUT, SGT, OD, STI, STT, TOL, TON, TSC, UFI, VNI, WEI, YUG, etc. It is preferable that it be one of these selected options. More preferably, it is one of the CHA type, FAU type, MFI type, LTA type, or RHO type, even more preferably CHA type, MFI type, LTA type, or RHO type, even more preferably MFI type or RHO type, and most preferably MFI type.

[0032] The thickness of the zeolite film is not particularly limited, but is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. This lower limit allows the film to perform well as a separation membrane. The upper limit of the film thickness is preferably 30 μm or less, more preferably 20 μm or less, and most preferably 10 μm or less. This upper limit prevents damage to the zeolite film due to thermal expansion, while simultaneously obtaining sufficient transmittance. The film thickness can be easily distinguished by the difference in density between the zeolite portion and the support portion using SEM, and can be measured by measuring several average locations using SEM observation. It is sufficient to measure five average locations and take the average value, preferably all five locations falling within the aforementioned range.

[0033] The zeolite membrane composite of the present invention relieves stress caused by thermal expansion and suppresses the occurrence of peeling and cracking of the zeolite membrane, and therefore exhibits its effects without limiting its applications. However, it is particularly effective when used at temperatures higher than room temperature, and is preferably applied to applications where it is used at 70°C or higher. As will be described later as an example of its application to a methanol production method, it can also be suitably used for the separation of ammonia and other substances.

[0034] <Method for producing zeolite membrane composites> Next, the method for producing the zeolite membrane composite of the present invention will be described. The present invention provides a method for producing a zeolite membrane composite using a commonly used method for producing a zeolite membrane on a general porous material. Methods for supporting the zeolite membrane include dipping, rubbing, suction, and impregnation. It is preferable to use microcrystals called seed crystals. These seed crystals serve as nuclei for growing the crystals that constitute the zeolite membrane.

[0035] In the method for producing a zeolite membrane composite according to the embodiment of the present invention, since seed crystals are supported inside a porous support, the D50 in the particle size distribution of the seed crystals is preferably 90% or less, more preferably 85% or less, and even more preferably 80% or less of the central pore diameter of the porous support. Furthermore, to prevent excessive penetration of the seed crystals into the porous support, it is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. Therefore, by setting the D50 (median diameter) in the particle size distribution of the seed crystals to the above ratio with respect to the central pore diameter of the porous support, the zeolite membrane formed on the porous support tends to become denser, and the methanol gas / hydrogen gas permeance ratio of the zeolite membrane composite tends to increase. The particle size distribution of the seed crystals can be measured using a laser-based particle size analyzer, and the central pore diameter of the porous support can be determined by pore distribution measurement using the mercury intrusion method.

[0036] The standard method for measuring the grain size distribution of seed crystals, as used in the analysis of the examples, is shown below.

[0037] (Device) Device name: SALD-2300 manufactured by Shimadzu Corporation Measurement method: Laser diffraction and laser scattering Measurement range: 0.017~2500μm Light source: Semiconductor laser (wavelength: 680nm, output: 3mW) Light receiving section: 78-element deformable concentric circle sensor, side sensor (1 element), rear sensor (5 elements), for a total of 84 light sensors.

[0038] (Measurement conditions) Sample concentration: 1 wt% Measurement unit: Flow cell Number of measurements: 1

[0039] (Analysis method) Software name: WingSALD TM II Refractive index setting: 1.35-0.001i Conversion to particle size distribution: volume-based

[0040] The method used in the analysis of the examples for measuring the central pore diameter of the porous support is shown below. In this invention, the central pore diameter is the value at which the cumulative frequency of pore diameters is 50%, meaning that half of all pores are above this value and the other half are below this value.

[0041] (Device) Device name: Micrometrics AutoPore IV9520

[0042] (Measurement conditions) Measurement pressure range: 3.45kPa to 414MPa Mercury surface tension: 485mN / m Mercury contact angle: 130°

[0043] The method for producing the zeolite membrane composite according to this embodiment preferably uses a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw material, alkali metal atom raw material, and water; a second step of mixing in silicon atom raw material; a third step of heating the mixture after the second step at 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step.

[0044] In the first step, a mixture containing at least an aluminum atom raw material, an alkali metal atom raw material, and water is prepared. The aluminum atom raw material is not particularly limited and includes aluminosilicate zeolite, amorphous aluminum hydroxide, aluminum hydroxide with a gibbsite structure, aluminum hydroxide with a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide, and aluminosilicate gel. Aluminosilicate zeolite, amorphous aluminum hydroxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide, and aluminosilicate gel are preferred, and aluminosilicate zeolite, amorphous aluminum hydroxide, sodium aluminate, and aluminosilicate gel are particularly preferred. These may be used individually or in combination of two or more. Examples of alkali metal atoms include Li, Na, K, Rb, Cs, and two or more of these metal atoms. Among these, Li, Na, and Cs are preferred, and Na is more preferred because it has excellent ammonia separation performance and is a commonly used alkali metal.

[0045] The alkali metal atom raw material is not particularly limited, and alkali metal hydroxides, alkali metal chlorides, etc., can be used. The metal species of these metal hydroxides are usually sodium (Na), potassium (K), lithium (Li), preferably Na and K, and more preferably Na. Furthermore, one metal species of metal oxide may be used alone, or two or more may be used in mixture.

[0046] Each material can be mixed by stirring. The stirring method is not particularly limited, but a three-in-one motor with stirring blades or a magnetic stirrer is preferred because it increases the solubility of the raw materials. To avoid changes in concentration due to the evaporation of water, it is desirable to mix in a closed system, and an air or nitrogen atmosphere is preferred.

[0047] In the second step, silicon atom raw materials are mixed with the mixture prepared in the first step. The silicon atom raw materials are not particularly limited, but examples include aluminosilicate zeolite, fumed silica, colloidal silica, amorphous silica, sodium silicate, methyl silicate, ethyl silicate, silicon alkoxides such as trimethylethoxysilane, tetraethyl orthosilicate, and aluminosilicate gel. Preferably, these include aluminosilicate zeolite, fumed silica, colloidal silica, amorphous silica, sodium silicate, methyl silicate, ethyl silicate, silicon alkoxide, and aluminosilicate gel. These may be used individually or in combination of two or more.

[0048] In the third step, the mixture from the second step is heated to 40°C or higher. The heating temperature is preferably 45°C or higher, and more preferably 50°C or higher. To avoid changes in concentration due to water evaporation, it is desirable to mix in a closed system, and an air or nitrogen atmosphere is preferred.

[0049] In the fourth step, water is mixed with the mixture after heating in the third step. By mixing in water, a raw material mixture for hydrothermal synthesis can be obtained. In the method for producing a zeolite membrane composite according to an embodiment of the present invention, the water content of the mixture prepared in the first step is preferably 30% to 80% by weight, more preferably 35% to 70% by weight, and even more preferably 40% to 60% by weight, of the water content of the hydrothermal synthesis raw material mixture. By using the above ratios, it is possible to promote the generation of precursors that contribute to the formation of the zeolite skeleton while maintaining fluidity suitable for mixing.

[0050] The present invention provides a method for producing a zeolite membrane composite, for example, by vertically immersing four porous supports, each with attached seed crystals, in a pressure vessel containing a mixture of raw materials for hydrothermal synthesis, sealing the vessel, and heating it in a constant temperature bath. At this time, from the viewpoint of promoting the crystallization of the zeolite membrane, the heating temperature is preferably 140°C or higher, more preferably 160°C or higher, and even more preferably 180°C or higher. From the viewpoint of avoiding weakening due to dissolution of the porous supports and the generation of impurity phases, the temperature is preferably 240°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower.

[0051] <Method for producing methanol> The methanol production method according to this embodiment is a methanol production method in which a raw material gas containing at least hydrogen and carbon monoxide and / or carbon dioxide is reacted in a reactor in the presence of a catalyst to obtain methanol, wherein the methanol produced by the reaction is extracted by permeating through a zeolite membrane composite. The raw gases are H2 and CO2. x It may contain other gases besides H2 and CO2. x Other gases include CH4, C2H4, C2H6, C3H6, C3H8, C4H8, and C4H 10 Examples include H2O, but H2 and CO x The content of other gases is usually 50% by volume or less.

[0052] When producing methanol from a raw material gas, known catalysts can be used, such as copper-based catalysts (copper-zinc catalysts, copper-chromium catalysts), zinc-based catalysts, chromium-based catalysts, and aluminum-based catalysts.

[0053] A zeolite membrane composite can be formed by, for example, preparing a cylindrical support, first supporting zeolite microcrystals within the pores, and then forming a zeolite membrane on the support. Hydrothermal synthesis can be used for zeolite growth, similar to zeolite synthesis. In this embodiment, the zeolite membrane composite described above can be used.

[0054] Figure 1 is a schematic cross-sectional view showing one embodiment of a reactor in which the present invention is implemented. Reactor 10 has a raw material feed inlet a, a permeate gas outlet b, and a non-permeate gas outlet c, and is made of a material that can withstand the high temperature and pressure environment in which the methanol production reaction takes place. In the figure there is only one inlet a, one outlet b, and one outlet c, but there may be multiple inlets a, one outlet b, and one outlet c. For example, the zeolite membrane composite 1 of the present invention is installed inside the reactor 10.

[0055] The zeolite membrane composite 1 is formed when a zeolite membrane is formed on a porous support. The shape of the porous support is not limited to tubular, but may be columnar, hollow columnar, or hollow honeycomb. One end of the zeolite membrane composite 1 is sealed by a cap 2, and the other end is connected to a pipe 3. The connection between the pipe 3 and the zeolite membrane composite 1, and the connection between the cap 2 and the zeolite membrane composite 1, is made by a bonding material. The method of connecting the zeolite membrane composite 1 is not limited to the above; for example, both ends may be connected to a pipe, allowing gas to flow inside.

[0056] A catalyst 13 is arranged around the tubular zeolite membrane complex 1. The raw material gas fed from the feed inlet a has methanol production promoted through contact with the catalyst 13. The generated methanol then permeates through the zeolite membrane of the zeolite membrane complex 1, allowing for the production of higher purity methanol. Furthermore, the selective permeation of methanol through the zeolite complex 1 reduces the methanol concentration in the gas in contact with the catalyst 13, thereby promoting methanol production.

[0057] The other end of piping 3 is connected to the permeate gas outlet b of the reactor, transferring methanol that has permeated through the zeolite membrane of the zeolite membrane complex 1 to the permeate gas outlet b. Alternatively, the zeolite membrane complex 1 may be connected directly to the permeate gas outlet b of the reactor without going through piping 3.

[0058] The reaction conditions are not particularly limited, but the reaction temperature is preferably between 200°C and 300°C. Note that the reaction temperature refers to the temperature inside the reactor. A reaction temperature of 200°C or higher increases the reaction rate and improves productivity. A reaction temperature of 300°C or lower creates a chemical equilibrium that is favorable for obtaining methanol, allowing for a higher conversion rate even if the film performance is somewhat inferior. Furthermore, the acceptable range of heat resistance required for the bonding material is also broadened.

[0059] The methanol obtained from the above reaction permeates through the zeolite membrane complex in the reactor, and the methanol is recovered from the permeate gas outlet of the reactor. The pressure inside the reactor when the generated methanol is permeated through the zeolite membrane composite, i.e., the pressure (gauge pressure) on the gas supply side of the zeolite membrane composite inside the reactor, is preferably 1 MPaG or higher, more preferably 2 MPaG or higher, preferably 8 MPaG or lower, and more preferably 5 MPaG or lower. By setting the pressure within an appropriate range, the equilibrium constraints of the reaction are reduced, and the reaction rate is improved, making it easier to achieve higher productivity. In addition, the increase in reactor manufacturing costs and raw material gas pressurization costs due to excessively high pressure can be suppressed. Furthermore, within the reaction vessel, the methanol partial pressure (absolute pressure) on the gas supply side of the zeolite membrane composite is preferably 0.1 MPaA or higher, more preferably 0.2 MPaA or higher, preferably 6 MPaA or lower, and more preferably 5 MPaA or lower. By setting the methanol partial pressure within this range, a sufficient amount of methanol permeates the membrane, and the membrane's effect is fully realized. On the other hand, within this range, the required durability and sealing performance of the joints do not become unnecessarily high, and joining can be done simply and in large quantities. The gauge pressure inside the reactor can be measured using a pressure gauge installed in the reactor. Furthermore, while the absolute pressure of methanol inside the reactor changes from upstream to downstream, here we will use the value calculated from the analysis results of the reactor outlet gas composition by gas chromatography and the gauge pressure as the absolute pressure of methanol inside the reactor. [Examples]

[0060] The present invention will be described in more detail below with reference to examples, but it goes without saying that the scope of the present invention is not limited to the embodiments shown in the following examples.

[0061] <Example 1> (Raw material mixture for hydrothermal synthesis) 1,714 g of 5 mol / L sodium hydroxide (manufactured by Kishida Chemical Co., Ltd.) and 4,266 g of demineralized water were mixed, and 33.4 g of sodium aluminate (manufactured by Kishida Chemical Co., Ltd., containing 62.2% by mass of Al2O3) was added and the mixture was stirred at 65°C for 30 minutes. 3,740 g of colloidal silica (manufactured by Nissan Chemical Corporation, Snowtex XS) was added to this mixture and the mixture was stirred at 65°C for 1.5 hours. Then, 9,654 g of demineralized water was added again to prepare the hydrothermal synthesis raw material mixture. The composition (molar ratio) of this hydrothermal synthesis raw material mixture was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.016 / 0.64 / 80.

[0062] (Porous support) As the porous support, a 100 cm alumina tube manufactured by Iwao Porcelain Industry Co., Ltd. (outer diameter 12 mm, inner diameter 9 mm, central pore diameter 0.814 μm) was washed with desalinated water and then dried.

[0063] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 10⁹, Na / Al molar ratio = 1.23, particle size distribution D50 = 0.60 μm) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15 mass%.

[0064] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 25 seconds, then dried at room temperature for 30 minutes and at 70°C for 2 hours to allow the seed crystals to adhere to the porous support. The excess seed crystals were removed by polishing with a rubber plate. The mass of the attached seed crystals was approximately 0.055 g. Four porous supports with attached seed crystals were prepared using this method. Four porous supports, each with a seed crystal attached, were immersed vertically in a Teflon® inner cylinder containing the aforementioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 3 hours. After 17 hours of standing heat under self-synthesis pressure, the composite was heated. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in demineralized water at 90°C for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh demineralized water at 90°C, the immersion and removal process was repeated a total of four times. The porous support-zeolite membrane composite was then dried at 100°C for 3 hours to obtain MFI-type zeolite membrane composite 1. For this zeolite membrane composite 1, the asymmetric reflection measurement results of the X-ray structural diffraction pattern are shown in Figure 2, the symmetric reflection measurement results in Figure 3, and the peak intensity ratio in Table 1. The mass of the zeolite membrane on the porous support was 1.032 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 2. The air permeability of zeolite membrane composite 1 at 50 Torr is 0.4 cm³. 3 It was / minutes.

[0065] <Example 2> (Raw material mixture for hydrothermal synthesis) 1,832 g of 5 mol / L sodium hydroxide (manufactured by Kishida Chemical Co., Ltd.) and 4,168 g of demineralized water were mixed, and 33.4 g of sodium aluminate (manufactured by Kishida Chemical Co., Ltd., containing 62.2% by mass of Al2O3) was added and the mixture was stirred at 70°C for 30 minutes. 3,740 g of colloidal silica (manufactured by Nissan Chemical Corporation, Snowtex XS) was added to this mixture and the mixture was stirred at 70°C for 2 hours. Subsequently, 9,654 g of demineralized water was added again to prepare the hydrothermal synthesis raw material mixture. The composition (molar ratio) of this hydrothermal synthesis raw material mixture was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.016 / 0.68 / 80.

[0066] (Porous support) As the porous support, a 100 cm alumina tube (outer diameter 12 mm, inner diameter 9 mm, central pore diameter 0.814 μm) manufactured by Iwao Porcelain Industry Co., Ltd. was used, which was washed with desalinated water and then dried.

[0067] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 10⁹, Na / Al molar ratio = 1.23, particle size distribution D50 = 0.60 μm) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15 mass%.

[0068] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 25 seconds, then dried at room temperature for 30 minutes and at 70°C for 2 hours to allow the seed crystals to adhere to the porous support. The excess seed crystals were removed by polishing with a rubber plate. The mass of the attached seed crystals was approximately 0.062 g. Four porous supports with attached seed crystals were prepared using this method. Four porous supports, each with a seed crystal attached, were immersed vertically in a Teflon® inner cylinder containing the aforementioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 1.25 hours. After that, the autoclave was left standing for 17 hours and heated under self-synthesis pressure. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in demineralized water at 90°C for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh demineralized water at 90°C, the immersion and removal operations were repeated a total of four times. The porous support-zeolite membrane composite was then dried at 100°C for 3 hours to obtain MFI-type zeolite membrane composite 2. For this zeolite membrane composite 2, the asymmetric reflection measurement results of the X-ray structural diffraction pattern are shown in Figure 4, the symmetric reflection measurement results in Figure 5, and the peak intensity ratio in Table 1. The mass of the zeolite film on the porous support was 1.162 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 2. The air permeability of the zeolite membrane composite at 50 Torr is 0.7 cm³. 3 It was / minutes.

[0069] <Comparative Example 1> (Raw material mixture for hydrothermal synthesis) 294 g of 99% sodium hydroxide (Kishida Chemical Co., Ltd., pelletized) and 4,196 g of demineralized water were mixed, and 22.5 g of sodium aluminate (Kishida Chemical Co., Ltd., containing 62.2% by mass of Al2O3) was added and the mixture was stirred at 65°C for 30 minutes. 3,796 g of colloidal silica (Nissan Chemical Corporation, Snowtex XS) was added to this mixture and the mixture was stirred at 65°C for 2 hours. Then, 14,231 g of demineralized water was added again to prepare the hydrothermal synthesis raw material mixture. The composition (molar ratio) of this hydrothermal synthesis raw material mixture was SiO2 / Al2O3 / NaOH / H2O = 1 / 0.012 / 0.64 / 100.

[0070] (Porous support) As the porous support, a 100 cm alumina tube manufactured by Iwao Porcelain Industry Co., Ltd. (outer diameter 12 mm, inner diameter 9 mm, central pore diameter 0.841 μm) was washed with desalinated water and then dried.

[0071] (Seed crystal dispersion) A seed crystal dispersion was prepared by grinding MFI-type zeolite (Na type, Si / Al molar ratio = 108, Na / Al molar ratio = 1.74, particle size distribution D50 = 1.2 μm) in a mortar and pestle, and then dispersing the seed crystals in water to a concentration of 0.15 mass%.

[0072] (Manufacturing of zeolite membrane composites) The porous support was immersed in the seed crystal dispersion described above for 20 seconds, then dried at room temperature for 30 minutes and at 70°C for 2 hours to allow the seed crystals to adhere to the porous support. The excess seed crystals were removed by polishing with a rubber plate. The mass of the attached seed crystals was approximately 0.048 g. Four porous supports with attached seed crystals were prepared using this method. Four porous supports, each with a seed crystal attached, were immersed vertically in a Teflon® inner cylinder containing the aforementioned hydrothermal synthesis raw material mixture. The autoclave was sealed, and the temperature was raised to 180°C in a constant temperature bath over 3 hours. After 17 hours of standing heat under self-synthesis pressure, the composite was heated. After the predetermined time had elapsed, the porous support-zeolite membrane composite was allowed to cool, removed from the reaction mixture, washed, and then immersed again in demineralized water at 90°C for 30 minutes. After 30 minutes, the zeolite membrane composite was removed from the demineralized water. Using fresh demineralized water at 90°C, the immersion and removal process was repeated a total of four times. The porous support-zeolite membrane composite was then dried at 100°C for 3 hours to obtain MFI-type zeolite membrane composite 3. For this zeolite membrane composite, the asymmetric reflection measurement results of the X-ray structural diffraction pattern are shown in Figure 6, the symmetric reflection measurement results in Figure 7, and the peak intensity ratio in Table 1. The mass of the zeolite membrane on the porous support was 0.977 g. Furthermore, a mixed gas of methanol (MeOH) and hydrogen (H2) was separated using a zeolite membrane composite, and the permeance (transmission rate) of each was measured, and the permeance ratio was calculated. The results are shown in Table 2. The air permeability of the zeolite membrane composite at 50 Torr is 2.5 cm³. 3 It was / minutes.

[0073] [Table 1]

[0074] [Table 2] [Industrial applicability]

[0075] It has been revealed that a high methanol gas / hydrogen gas permeance ratio can be obtained when producing methanol using the zeolite membrane composite of the present invention. Furthermore, since the principle by which this high permeance is obtained is common to other reactions as well, it can be applied to various reactions requiring separation, and as a zeolite separation membrane that can obtain high permeance, it is a technology with high industrial value. [Explanation of symbols]

[0076] 1. Zeolite membrane complex 2 caps 3 Piping 10 Reactors 13 Catalyst

Claims

1. A zeolite membrane composite having a zeolite membrane on a porous support, wherein the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° in an asymmetric reflection measurement with a fixed incident angle θ1 is at least one times that of the peak intensity around 2θ = 23.1°.

2. The zeolite film composite according to claim 1, wherein the peak intensity of the X-ray diffraction pattern around 2θ = 23.7° in a symmetric reflection measurement without fixing the incident angle θ2 is 0.65 times or more and less than 1.00 times the peak intensity around 2θ = 23.1°.

3. The zeolite membrane composite according to claim 1 or 2, wherein the zeolite is of the MFI type.

4. A method for producing a zeolite membrane composite, wherein the D50 in the particle size distribution of the seed crystal is 90% or less of the central pore diameter of the porous support.

5. A method for producing a zeolite membrane composite according to claim 4, using a hydrothermal synthesis raw material mixture prepared by a method comprising: a first step of preparing a mixture containing at least aluminum atom raw materials, alkali metal atom raw materials, and water; a second step of mixing in silicon atom raw materials; a third step of heating the mixture after the second step at 40°C or higher; and a fourth step of mixing water with the mixture after heating in the third step.

6. A method for producing methanol, comprising reacting a raw material gas containing at least hydrogen, carbon monoxide and / or carbon dioxide in a reactor in the presence of a catalyst, wherein the methanol produced by the reaction is extracted by permeating through the zeolite membrane composite described in claim 1 or 2.

Citation Information

Patent Citations

  • Method for producing methanol

    JP1997511509A

  • Reactor for producing methanol and method for producing methanol

    JP2007055970A

  • Method of carrying out chemical equilibrium reaction using permselective membrane

    JP2016117726A

  • Zeolite separation membrane and separation module

    JP2016174996A